EVOLUTIONARY, BIOLOGICAL AND HUMAN PERSPECTIVES ON THE NATURE AND CAUSES OF WARS: USING INDIVIDUAL LEVEL OF ANALYSIS APPROACH - Anyalebechi, Shammah Mahakwe, PhD; Augustina Ikechukwu, PhD (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The domain of warfare has traditionally been scrutinized through macro lenses such as geopolitics and military strategy, yet a comprehensive understanding requires delving into the individual dimension, which incorporates the insights from evolutionary, biological, and human nature perspectives. Despite considerable investigations into the origins and repercussions of war, the subtle yet critical influences exerted by individual-level determinants warrant further exploration. This research endeavors to unravel how inherent human traits—namely aggression, empathy, fear, and the quest for belonging—meld with our evolutionary and biological underpinnings to mold individual conduct in wartime scenarios. Grasping these elements is crucial to decipher the underlying reasons for individual engagement in war and the ensuing psychological ramifications, which bear significant relevance for crafting effective conflict resolution and recovery strategies. By anchoring this study within the Individual Level of Analysis of War and leveraging a qualitative methodology, specifically content analysis, this investigation meticulously reviews scholarly works, autobiographical narratives, and case studies to dissect the intricacies of individual experiences in war. Findings elucidate that personal-level variables critically inform combatant behavior and wartime experiences, where evolutionary and biological predispositions converge with sociocultural factors to influence wartime actions. Recommendations include embedding psychological support and conflict mediation training in military and post-conflict rehabilitation frameworks, aiming to modulate aggression and enhance empathic competencies